MADATYAYA (ALCOHOL INTOXICATION) A REVIEW - Nilesh M. Rajmane; Deepak S. Wali; Ankur A. Kadam (International Journal of Applied Ayurved Research, 2017)
Madya (Alcohol) is explained under Ahara Varga. It is used as Pana, as Anupana and also as Aoushadhi. It is also used in Shastra Karma as Sandnyahar (Anasthetic), The excess intake of Madya is known as Madatyaya, leads to toxic effects and may also result in Ojakshaya. The habit of alcohol consumption leads to its addiction and causes alcohol intoxication. In the present study an effort is made to review Madatyaya from the available classics of Ayurved in Charak Samhita the various Awasthas in an individual becoming addicted with Madya is elaborated. Susharut used Panatyaya term in the place of Madatyaya and accepts four types of Panatyaya viz. Vatakrita, Pittakrita, Kaphakrita and Sarvakrita. According to Vagbhat and Yogaratnakar the severity of disease Madatyaya will persist for seven or eight days. According to Kashyapa Madatyaya is Amaja, that is why while treating Madatyaya, Langhana should be done first. The ailments caused by Madya in Mithyaa – Atiyoga -Heenayoga can be cured by taking the Madya in proper way and quantity (Samayoga). Here the same type of Madya or other varieties of Madya can be given. All the types of Madatyaya are of Tridoshaja. Therefore, in the beginning, treatment should be done for the most predominant Dosha.